2018
DOI: 10.3354/dao03230
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing, validating, and field testing a multiplex qPCR for the detection of amphibian pathogens

Abstract: Amphibian populations worldwide are facing numerous threats, including the emergence and spread of infectious diseases. In the past 2 decades, Batrachochytrium dendrobatidis (Bd), a parasitic fungus, and a group of viruses comprising the genus Ranavirus have become widespread and resulted in mass mortality events and extirpations worldwide. In 2013, another novel fungus, B. salamandrivorans (Bsal), was attributed to dramatic declines in populations of fire salamander Salamandra salamandra in the Netherlands. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…A synthetic gene block (gBlock ® ; Figure ) was utilized for optimization and quantification purposes. The gBlock was rehydrated, quantified and diluted as described previously (Standish et al, ), resulting in a standard curve of 10‐fold dilutions ranging from 10 7 to 1 copy reaction −1 . Initial steps were taken to optimize and validate the assay prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…A synthetic gene block (gBlock ® ; Figure ) was utilized for optimization and quantification purposes. The gBlock was rehydrated, quantified and diluted as described previously (Standish et al, ), resulting in a standard curve of 10‐fold dilutions ranging from 10 7 to 1 copy reaction −1 . Initial steps were taken to optimize and validate the assay prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Field studies suggested that co-occurring Bd and Ranavirus can, in some cases, have positive effects on each other [ 8 , 61 , 165 , 166 ]. Still, this interaction was not confirmed in other cases [ 61 , 159 , 164 , 167 ] or even turned negative [ 165 , 168 ] (Table 2 ). A lower Bd or Ranavirus infection intensity in individuals co-infected by both parasites compared to single infections may arise from an enhanced immune response of the host or the interspecific competition between the agents [ 166 ].…”
Section: Co-infection By Heterologous Parasitesmentioning
confidence: 94%
“…Extracted DNA from skin swabs was used to screen for Batrachochytrium dendrobatidis ( Bd ), B. salamandrivorans ( Bsal ), and the ranavirus frog virus 3 (FV3). Multiplex quantitative PCR was conducted as described by Standish et al (2018).…”
Section: Methodsmentioning
confidence: 99%